Democratic dialogue and the constitution - Young, Alison L. (New York, NY : Oxford University Press, 2017)
This book evaluates dialogue in the UK constitution, assessing the protection of human rights through the Human Rights Act 1998, the common law, and EU law. It also evaluates court-court dialogue between the UK court, the European Court of Justice, and the European Court of Human Rights. The conclusion evaluates the implications of the proposed British Bill of Rights and the referendum decision to leave the European Union --Front flap of book.
Introduction -- The problem with control -- Democratic dialogue and the dynamic approach -- Re-defining democratic dialogue -- Inter-institutional interactions -- From inter-institutional interactions to democratic dialogue -- Democratic dialogue and the UK Constitution -- Democratic dialogue and UK human rights law -- Dialogue between courts -- Conclusion.
Includes bibliographical references and index.
Keywords: Great Britain; Human Rights Act 1998 (Great Britain); Constitutional law -- Great Britain; Constitutional history -- Great Britain; Law; Constitutional history; Constitutional law; Politics and government; Law; Great Britain -- Politics and government; Great Britain